Business Process Modeling Patterns for Blockchain Application Development - Fouzia Alzhrani; Kawther Saeedi; Liping Zhao (IEEE Access)
Despite the significant potential of blockchain technology to transform e-business through smart contracts, developing blockchain applications remains a challenging task. A critical gap exists in the software development process, where the analysis and design phases are not adequately integrated. This gap is exacerbated by the lack of a standardized approach to modeling blockchain application requirements, which hinders effective communication between requirement analysis and software design. To address this gap, this study proposes a comprehensive collection of data-driven patterns for business process modeling, comprising nine patterns that capture various blockchain-specific aspects, including token circulation, supply, and authorization, as well as smart contract security and authorization. Through a trend analysis of real-world blockchain applications, we identified recurring business processes across domains and validated our patterns by comparing them to existing literature and a proof-of-concept application. The results reveal statistically significant trends in blockchain business processes, providing a foundation for future research in this area. Specifically, the analysis of patterns in different domains (e.g., marketplace, game, finance, and media) shows some interesting trends: Transfer patterns are most common in marketplace and game applications; lifecycle patterns are most common in game applications; and accessibility patterns are most common in marketplace, finance, IT, and game applications. Our contribution provides a standardized framework for modeling blockchain application requirements, enabling software developers to better understand the complex needs of blockchain applications and design more effective solutions.